2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the thickness and nonlinear elasticity of tissue on the success of surgical stapling for laparoscopic liver resection

Abstract: Recently, the range of applications of surgical staplers has been extended to include laparoscopic liver resection because manipulation of a surgical stapler is very simple. Revealing the causes of stapling failure and suggesting a method to solve stapling failure are important for safe laparoscopic liver resection. Surgeons say that tissues make stapling more likely to fail if they are thick and brittle. However, the combinatorial effect of the thickness and stiffness of tissues on the success of surgical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…22 Other factors affecting stapler use are tissue thickness and stiffness; stapling failure has been found to increase with increasing tissue thickness, and it has been suggested that tissue thickness has a greater effect on stapler success compare with tissue stiffness. 27,28 We report similar findings in this study; the right division lobes were assessed to be too challenging for stapler resection in all cadavers due to anatomic location as well as increased lobe thickness. In cadavers >15 kg, all liver lobes were considered too thick for staple resection, with most attempted resections resulting in incomplete closure of the stapler and/or staples.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…22 Other factors affecting stapler use are tissue thickness and stiffness; stapling failure has been found to increase with increasing tissue thickness, and it has been suggested that tissue thickness has a greater effect on stapler success compare with tissue stiffness. 27,28 We report similar findings in this study; the right division lobes were assessed to be too challenging for stapler resection in all cadavers due to anatomic location as well as increased lobe thickness. In cadavers >15 kg, all liver lobes were considered too thick for staple resection, with most attempted resections resulting in incomplete closure of the stapler and/or staples.…”
Section: Discussionsupporting
confidence: 80%
“…If a stapler is used inappropriately for hepatic vascular division, staple line disruption can occur and potentially lead to significant hemorrhage; however, with correct stapler use, reported incidence of this complication is rare 22 . Other factors affecting stapler use are tissue thickness and stiffness; stapling failure has been found to increase with increasing tissue thickness, and it has been suggested that tissue thickness has a greater effect on stapler success compare with tissue stiffness 27,28 . We report similar findings in this study; the right division lobes were assessed to be too challenging for stapler resection in all cadavers due to anatomic location as well as increased lobe thickness.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations